Cav1 suppresses tumor growth and metastasis in a murine model of cutaneous SCC through modulation of MAPK/AP-1 activation - Trimmer, Casey; Bonuccelli, Gloria; Katiyar, Sanjay; Sotgia, Federica; Pestell, Richard G; Lisanti, Michael P; Capozza, Franco (The American journal of pathology, 2013)
Caveolin-1 (Cav1) is a scaffolding protein that serves to regulate the activity of several signaling molecules. Its loss has been implicated in the pathogenesis of several types of cancer, but its role in the development and progression of cutaneous squamous cell carcinoma (cSCC) remains largely unexplored. Herein, we use the keratinocyte cell line PAM212, a murine model of cSCC, to determine the function of Cav1 in skin tumor biology. We first show that Cav1 overexpression decreases cell and tumor growth, whereas Cav1 knockdown increases these attributes in PAM212 cells. In addition, Cav1 knockdown increases the invasive ability and incidence of spontaneous lymph node metastasis. Finally, we demonstrate that Cav1 knockdown increases extracellular signaling-related kinase 1/2 mitogen-activated protein kinase/activator protein-1 pathway activation. We attribute the growth and invasive advantage conferred by Cav1 knockdown to increased expression of activator protein-1 transcriptional targets, including cyclin D1 and keratin 18, which show inverse expression in PAM212 based on the expression level of Cav1. In summary, we demonstrate that loss of Cav1 affects several characteristics associated with aggressive human skin tumors and that this protein may be an important modulator of tumor growth and invasion in cSCC.